How healing works : get well and stay well using your hidden power to heal - Jonas, Wayne B. (Lorena Jones Books, an imprint of Ten Speed Press, 2018)
"Drawing on 40 years of research and patient care, Dr. Wayne Jonas explains how 80 percent of healing occurs organically and how to activate the healing process. In How Healing Works, Dr. Wayne Jonas lays out a revolutionary new way to approach injury, illness, and wellness. Dr. Jonas explains the biology of healing and the science behind the discovery that 80 percent of healing can be attributed to the mind-body connection and other naturally occurring processes. Jonas details how the healing process works and what we can do to facilitate our own innate ability to heal. Dr. Jonas's advice will change how we consume health care, enabling us to be more in control of our recovery and lasting wellness. Simple line illustrations communicate statistics and take-aways in a memorable way. Stories from Dr. Jonas's practice and studies further illustrate his method for helping people get well and stay well after minor and major medical events"--